asma.sahraoui@univ-mosta.dz - صحراوي أسماء (International Journal of Social Communication, 2023)
Invading user contexts, penetrating into them, campaigns to attack them, surround them with content wherever they are, and entrapment of streaming content describe the inevitability of receiving content, which is another avenue of symbolic violence. There are not enough options to avoid exposure to the filteredand not skippable content machine Accordingly, the expected effects of the symbolic violence practiced as a result of the visualization and traffic of the content deny freedom and different points of view and establish an awareness industry. according to complex criteria. This qualitative study seeks, by employing the participatory observation tool on the most intensively used platforms by the Algerian user, to identify the manifestations of symbolic violence that perpetuate the inevitability of exposure to content.